2019
DOI: 10.1111/emip.12282
|View full text |Cite
|
Sign up to set email alerts
|

A Topical and Methodological Systematic Review of Meta‐Analyses Published in the Educational Measurement Literature

Abstract: This systematic review investigated the topics studied and reporting practices of published meta‐analyses in educational measurement. Our findings indicated that meta‐analysis is not a highly utilized methodological tool in educational measurement; on average, less than one meta‐analysis has been published per year over the past 30 years (28 meta‐analyses were published between 1986 and 2016). Within the field, researchers have utilized meta‐analysis to study three primary subject areas: test format effects, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…There have been several (methodological) reviews on the occurrence of dependent effect sizes. A recent review of 28 meta-analyses from educational research found that 57% of the studies reported dependent effect sizes (Rios et al, 2020). This is similar to the findings of Ahn and colleagues (2012), who found that of the 56 meta-analyses on educational research they reviewed, 62% reported multiple (dependent) effect sizes, and a review of 44 meta-analyses on randomized controlled trials reported that 70% of the studies included dependent effect sizes (Page et al, 2015).…”
Section: Meta-analytic Structural Equation Modelingmentioning
confidence: 99%
“…There have been several (methodological) reviews on the occurrence of dependent effect sizes. A recent review of 28 meta-analyses from educational research found that 57% of the studies reported dependent effect sizes (Rios et al, 2020). This is similar to the findings of Ahn and colleagues (2012), who found that of the 56 meta-analyses on educational research they reviewed, 62% reported multiple (dependent) effect sizes, and a review of 44 meta-analyses on randomized controlled trials reported that 70% of the studies included dependent effect sizes (Page et al, 2015).…”
Section: Meta-analytic Structural Equation Modelingmentioning
confidence: 99%